Peer Acceptance in the School Class and Subjective Health Complaints: A Multilevel Approach. (11th September 2013) - Almquist, Ylva B.; Modin, Bitte; Augustine, Lilly
ABSTRACT: BACKGROUND: Feeling accepted by peers is important for young people's health but few studies have examined the overall degree of acceptance in school and its health consequences. The purpose of the study was to investigate whether health complaints among Swedish students can be attributed to the acceptance climate in their school class even when the health effects of their own (individual) acceptance score have been taken into account. METHODS: The data used were from the Health Behaviour in School‐aged Children (HBSC) study for the years 2001 to 2002, 2005 to 2006, and 2009 to 2010, consisting of 13, 902 5th‐, 7th‐, and 9th‐grade Swedish students nested into 742 school classes. The statistical analyses were performed by means of linear regression multilevel analysis. RESULTS: The results indicated that the variation in subjective health complaints could be ascribed partly to the school‐class level (boys: 5.0%; girls: 13.5%). Peer acceptance at the individual level demonstrated a clear association with health: the lower the acceptance, the higher the complaint scores. For girls, but not for boys, the overall degree of peer acceptance in the school class demonstrated a contextual effect on health, net of acceptance at the student level. Interaction analyses also revealed an increasingly favorable health among poorly accepted girls as the acceptance climate in the school class declined. CONCLUSIONS: A lower overall degree of peer acceptance in the school class is associated with poorer health among girls. However, girls who themselves feel poorly accepted are not as negatively affected health‐wise by a poor acceptance climate, as are well‐accepted girls.